Pemanfaataan Daerah Tujuan Wisata melalui Program Penggalian dan Pemetaan Warisan Budaya Lokal untuk Pencapaian SDGs - Nonny Basalama; Rahman Taufiqrianto Dako (Univeristas Negeri Gorontalo, 2022)
In the context of developing a tourist destination village in the Tomini Bay area, it is necessary to carry out various strategies in achieving the SDGs. One of the proposed programs is to promote regional top cultural tourism. However, due to the lack of information obtained by tourists, some sectors of cultural tourism are still untouched by tourists. So to overcome these problems, a mapping of the objects of local cultural tourism heritage has been carried out which will be implemented into a system that presents information in the form of locations and detailed descriptions of these local cultural tourism objects. The tourism destination villages are the Village of Sosial and Molombulahe, Paguyaman District, Boalemo Regency. Through the Village Development Community Service Program, this program has been designed with village officials and the community related to problem solving in finding solutions through excavation and mapping of local culture for the achievement of SDGs in Paguyaman District. The results obtained are the mapped